Circulating miR-147b as a diagnostic marker for patients with bacterial sepsis and septic shock. - Ngo Tat Trung; Tran Thi Lien; Vu Viet Sang; Nghiem Xuan Hoan; Nguyen Dang Manh; Nguyen Sy Thau; Dao Thanh Quyen; Tran Thi Thu Hien; Phan Quoc Hoan; Mai Hong Bang; Thirumalaisamy P Velavan; Le Huu Song (PLoS ONE)
Background Early diagnosis, precise antimicrobial treatment and subsequent patient stratification can improve sepsis outcomes. Circulating biomarkers such as plasma microRNAs (miRNAs) have proven to be surrogates for diagnosis, severity and case management of infections. The expression of four selected miRNAs (miR-146-3p, miR-147b, miR-155 and miR-223) was validated for their prognostic and diagnostic potential in a clinically defined cohort of patients with sepsis and septic shock. Methods The expression of plasma miRNAs was quantified by quantitative PCR (qPCR) in patients with bacterial sepsis (n = 78), in patients with septic shock (n = 52) and in patients with dengue haemorrhagic fever (DHF; n = 69) and in healthy controls (n = 82). Results The expression of studied miRNA was significantly increased in patients with bacterial sepsis and septic shock. The plasma miR-147b was able to differentiate bacterial sepsis from non-sepsis and septic shock (AUC = 0.77 and 0.8, respectively, p≤ 0.05), while the combination of plasma miR-147b and procalcitonin (PCT) predicted septic shock (AUC = 0.86, p≤ 0.05). Conclusions The plasma miR-147b may be an useful biomarker independently or in combination with PCT to support clinical diagnosis of sepsis and equally prognosis of patients with septic shock.